Metabolic switch and epithelial–mesenchymal transition cooperate to regulate pluripotency. (24th February 2020) - Sun, Hao; Yang, Xiao; Liang, Lining; Zhang, Mengdan; Li, Yuan; Chen, Jinlong; Wang, Fuhui; Yang, Tingting; Meng, Fei; Lai, Xiaowei; Li, Changpeng; He, Jingcai; et al.
Abstract: Both metabolic switch from oxidative phosphorylation to glycolysis (OGS) and epithelial–mesenchymal transition (EMT) promote cellular reprogramming at early stages. However, their connections have not been elucidated. Here, when a chemically defined medium was used to induce early EMT during mouse reprogramming, a facilitated OGS was also observed at the same time. Additional investigations suggested that the two events formed a positive feedback loop via transcriptional activation, cooperated to upregulate epigenetic factors such as Bmi1, Ctcf, Ezh2, Kdm2b, and Wdr5, and accelerated pluripotency induction at the early stage. However, at late stages, by over‐inducing glycolysis and preventing the necessary mesenchymal–epithelial transition, the two events trapped the cells at a new pluripotency state between naïve and primed states and inhibited further reprogramming toward the naïve state. In addition, the pluripotent stem cells at the new state have high similarity to epiblasts from E4.5 and E5.5 embryos, and have distinct characteristics from the previously reported epiblast‐like or formative states. Therefore, the time‐dependent cooperation between OGS and EMT in regulating pluripotency should extend our understanding of related fields. Synopsis: Whether the switch from oxidative phosphorylation to glycolysis (OGS) and epithelial‐mesenchymal transition (EMT) are functionally linked during nuclear reprogramming is unclear. Here, multi‐layered analysis of mouse iPSC generation uncovers stage‐specific interdependences between EMT and metabolism, controlling an intermediary pluripotent state. EMT and OGS induced by a chemically‐defined medium cooperate and reduce epigenetic barriers at early stages of reprogramming. EMT and OGS maintain increased glycolytic and epithelial markers at late stages of reprogramming. Intermediate pluripotent cells can be converted to naïve and primed states. Intermediate pluripotent cells resemble gene expression of the E5.5 embryo epiblast. Abstract : Stage‐specific synergy between EMT and energy metabolism defines a new intermediate state in reprogramming.